2020
DOI: 10.1155/2020/2141508
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Improves Inflammatory Responses of Diabetes Mellitus in Zucker Diabetic Fatty Rats and Insulin-Resistant HepG2 Cells through the PPM1B Pathway

Abstract: Berberine (BBR), a natural compound extracted from a Chinese herb, has been shown to effectively attenuate insulin resistance (IR) and inflammation in the clinic. However, its ameliorative mechanism against IR is not well defined. This study is aimed at investigating the effect of BBR and protein phosphatase, Mg2+/Mn2+-dependent 1B (PPM1B) on IR. Biochemical measurements and liver histopathology were detected using the biochemical analyzer and HE staining in ZDF rats, respectively. Microarray analysis of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The main active ingredients in this formula, which were measured by HPLC, include geniposide, berberine, palmatine, etc ( YANG et al, 2019 ). These ingredients were found to be effective in treating T2DM through a variety of mechanisms ( Gu et al, 2010 ; Zhang et al, 2010 ; Li et al, 2019a ; Li et al, 2019b ; Mi et al, 2019 ; Sun et al, 2020a ; Sun et al, 2020b ; Wu et al, 2020 ). A series of clinical studies have been carried out on the treatment of T2DM with HLJDD, and promising results have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredients in this formula, which were measured by HPLC, include geniposide, berberine, palmatine, etc ( YANG et al, 2019 ). These ingredients were found to be effective in treating T2DM through a variety of mechanisms ( Gu et al, 2010 ; Zhang et al, 2010 ; Li et al, 2019a ; Li et al, 2019b ; Mi et al, 2019 ; Sun et al, 2020a ; Sun et al, 2020b ; Wu et al, 2020 ). A series of clinical studies have been carried out on the treatment of T2DM with HLJDD, and promising results have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 […”
Section: Discussionmentioning
confidence: 99%
“…In addition, BBR inhibited the lipopolysaccharide (LPS)/tolllike receptor 4 (TLR4)/tumor necrosis factor-α (TNF-α) pathway, suggesting that this pathway may be one of the BBR mechanisms to lower blood glucose and moderate IR [50]. Moreover, Wu et al demonstrated that BBR may alleviate IR via regulation on the protein phosphatase, Mg 2+ / Mn 2+ -dependent 1B (PPM1B) signaling pathway, including the PPM1B/inhibitor kappa B kinaseβ (IKKβ)/nuclear factor κB (NF-κB), and PPM1B/GLUT4 pathways [51]. [73].…”
Section: Increasing Insulin Sensitivity and Alleviating Irmentioning
confidence: 99%